Olfactory disorders in patients with chronic rhinosinusitis in Kinshasa, Democratic Republic of the Congo: A cross-sectional study - Nsunzu Tshingamb, Yasmin; Mpiana, Sympho Junior; Sekele Marob Ndjock , Patrick; Kayembe, Emile; Banza Lukoji , Eric; Ntumba Malemba , Alain; Omadjela, Auguste O.; Nyembue, Dieudonné T. (Orapuh Journal, 2025)
Introduction Approximately three-quarters of patients with chronic rhinosinusitis (CRS) develop an olfactory disorder (OD). Due to its gradual onset and subtle nature, many CRS patients are unaware of their OD, making its assessment and prevalence difficult. Objective This study aimed to assess the frequency of ODs and the characteristics of CRS patients in a hospital setting in Kinshasa. Methods This was a cross-sectional and analytical study involving 105 CRS patients in two medical facilities in Kinshasa. Eligible patients were aged ≥18 years, diagnosed with CRS, had completed primary education, and provided informed consent. The ASOF questionnaire and the Sniffin’ Sticks Test (SST) were used for subjective and/or objective olfactory assessment. Univariate analyses were performed to describe statistics for variables of interest. Frequencies were calculated for qualitative variables, while the mean (SD) was reported for quantitative variables. Proportions were compared using the Chi-square test, and the Student’s t-test was used to compare means. Results The average age of patients was 40.3 ± 1.4 years, with a higher number of females. Allergic comorbidities were the most commonly reported in patient histories. Subjectively, only 22.9% of patients reported an altered sense of smell; however, using the SST, 63.8% of CRS patients were found to have an OD, primarily hyposmia. All mean scores for subjective and objective olfactory assessments were significantly higher (p < 0.001) among CRS patients with OD compared to those without. Additionally, the mean VAS level for loss of smell was higher in CRS patients with OD (p < 0.001). Patients with OD were significantly older than those without (42.6 ± 5.3 years vs. 36.3 ± 13.3 years; p = 0.035). Conclusion This study demonstrates that ODs are common in CRS, particularly among older patients. Olfactory assessment should be implemented to ensure effective diagnosis and management of rhinological conditions.